(3eNJUQ CHj YhGfIs - (3jYbhH Hf ESMGb Hf EHQGgje GdfjSGHhQqi Ke GdCSaQGjjfj, CHh YhGfI,J (B316 (3g` s ((3OGQ GdMOjK HOeTb s)
(3ChdgG (B:s
(3jHJOF HHGH GdJjee ddLfGHI EPG hLO GdeGA dZSd LSOg s
(3BNQgG (B:s
(3hjfJgi HHG HjGf ebOGQ GdSJQI GdJi dGjVQ GdeUdi ef jeQ Hjf jOjg ef QhGFgG s
(3ef fSNI CNQis
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B196 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B242s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B4 - (3U (B97 s
Keywords: (3GdMOjK h GdeUWdMs